PENGUATAN MANAJEMEN ORGANISASI LOKAL DALAM PENCEGAHAN PENYALAHGUNAAN NARKOTIKA, PSIKOTROPIKA, DAN ZAT ADIKTIF DI BANDUNG - Saputra, Putra Pratama (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2017)
AbstractThe drug abuse problem that occurs in society these days is very alarming. The existence of the perpetrator and the activity of drug abuse have become a custom of the community. However, permissiveness has shown as if the people let these problems occur. The existence of stakeholders is expected to have a positive impact, so that the functions of society can work well, especially in the prevention of drug abuse. Strengthening the management of local organizations is an effort to prevent drug abuse. This research aims to produce the right model for strengthening the management of local organizations in efforts to prevent drug abuse. The method used in this research is a qualitative research method with action research. The Place of research conducted in RW 18 Sadang Serang Village, Coblong Sub-district, Bandung with a number of main informants and supporting informant were 9 people out of 7 people. The intervention is done through several activities, namely the Development of Local Organizations